Challenges involved in cell therapy for Parkinson’s disease using human pluripotent stem cells - Moon, Heechang; Kim, Bokwang; Kwon, Inbeom; Oh, Yohan (Frontiers in Cell and Developmental Biology, 2023)
Neurons derived from human pluripotent stem cells (hPSCs) provide a valuable tool for studying human neural development and neurodegenerative diseases. The investigation of hPSC-based cell therapy, involving the differentiation of hPSCs into target cells and their transplantation into affected regions, is of particular interest. One neurodegenerative disease that is being extensively studied for hPSC-based cell therapy is Parkinson’s disease (PD), the second most common among humans. Various research groups are focused on differentiating hPSCs into ventral midbrain dopaminergic (vmDA) progenitors, which have the potential to further differentiate into neurons closely resembling DA neurons found in the substantia nigra pars compacta (SNpc) after transplantation, providing a promising treatment option for PD. In vivo experiments, where hPSC-derived vmDA progenitor cells were transplanted into the striatum or SNpc of animal PD models, the transplanted cells demonstrated stable engraftment and resulted in behavioral recovery in the transplanted animals. Several differentiation protocols have been developed for this specific cell therapy. However, the lack of a reliable live-cell lineage identification method presents a significant obstacle in confirming the precise lineage of the differentiated cells intended for transplantation, as well as identifying potential contamination by non-vmDA progenitors. This deficiency increases the risk of adverse effects such as dyskinesias and tumorigenicity, highlighting the importance of addressing this issue before proceeding with transplantation. Ensuring the differentiation of hPSCs into the target cell lineage is a crucial step to guarantee precise therapeutic effects in cell therapy. To underscore the significance of lineage identification, this review focuses on the differentiation protocols of hPSC-derived vmDA progenitors developed by various research groups for PD treatment. Moreover, in vivo experimental results following transplantation were carefully analyzed. The encouraging outcomes from these experiments demonstrate the potential efficacy and safety of hPSC-derived vmDA progenitors for PD cell therapy. Additionally, the results of clinical trials involving the use of hPSC-derived vmDA progenitors for PD treatment were briefly reviewed, shedding light on the progress and challenges faced in translating this promising therapy into clinical practice.